Service differentiation using priority-based MAC protocol in MANETs. (29th September 2010) - Sarma, Nityananda; Nandi, Sukumar
Multihop wireless network has emerged recently as an evolution of wireless network technology and is likely to be the integral part of future communication environment. In this context, support for quality of service (QoS) is becoming an inherent necessity, rather than an additional feature of the network. In this paper, we propose a priority-based variant of the IEEE 802.11 DCF for providing service differentiation at the MAC layer of MANETs. The channel access priorities are realised with a backoff timer selection scheme. Further, differentiating relayed traffic from self-generated traffic, improves both end-to-end QoS performance and overall network utilisation in multihop environments. A priority-based queue management and packet scheduling is implemented to improve the intra-node service differentiation. Performance analysis for single hop scenarios is done using a Markov chain model whose accuracy is validated through simulation. Furthermore, simulation studies in multihop scenarios show suitability of the proposed scheme to provide an enhanced level of service differentiation.